2022
DOI: 10.1038/s41558-022-01312-w
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging social cognition to promote effective climate change mitigation

Abstract: Effective climate change mitigation is a social dilemma: the benefits are shared collectively while the costs are often private. To solve this dilemma, we argue that we must first understand the nature of human cooperation. This constitutes a shift in the field of psychology and climate change, which has traditionally focused more intensely on risk-perception, miscommunication or time discounting, to explain the lack of climate action. We review three social cognition mechanisms that regulate cooperation: norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 107 publications
0
12
0
Order By: Relevance
“…One can speculate that this could be the case if the active behaviour is individually costly and perceived as a moral duty. In this case, the active individuals behave as cooperators whose efforts (measured in terms of opportunity cost) are influenced the most by the observation of the others’ efforts [35, 5].…”
Section: Discussionmentioning
confidence: 99%
“…One can speculate that this could be the case if the active behaviour is individually costly and perceived as a moral duty. In this case, the active individuals behave as cooperators whose efforts (measured in terms of opportunity cost) are influenced the most by the observation of the others’ efforts [35, 5].…”
Section: Discussionmentioning
confidence: 99%
“…Here, social interactions are also rewarding. Thus it has been suggested that climate-friendly behavior promoted by one’s peers can encourage other to shift toward the same type of behavior ( Boon-Falleur et al, 2022 ). Since the DA system has also been identified in social behavior encoding ( Klein and Platt, 2013 ; Gunaydin et al, 2014 ; Munuera et al, 2018 ), using social strategies to curve climate change sounds like a valid approach.…”
Section: Suggestion 2: Promote Climate-friendly Behavior Through Intr...mentioning
confidence: 99%
“…Climate change is nowadays considered a serious threat that is already underway. Despite this growing awareness, efforts to mitigate climate change have fallen short in recent decades [1]. However, there are clear signs of a reaction.…”
Section: Introductionmentioning
confidence: 99%